Surgical treatment of intracranial aneurysms: six-year experience in Belo Horizonte, MG, Brazil - Costa Jr,Leodante Batista da (2004)
Spontaneous subarachnoid hemorrhage accounts for 5 to 10 % of all strokes, with a worldwide incidence of 10.5 / 100000 person/year, varying in individual reports from 1.1 to 96 /100000 person/year. Angiographic and autopsy studies suggest that between 0.5% and 5% of the population have intracranial aneurysms. Approximately 30000 people suffer aneurysmal subarachnoid hemorrhage in the United States each year, and 60% die or are left permanently disabled. We report our experience in the surgical treatment of intracranial aneurysms in a six year period, in Belo Horizonte, Minas Gerais, Brazil. We reviewed the hospital files, surgical and out-patient notes of all patients operated on for the treatment of intracranial aneurysms from January 1997 to January 2003. Four hundred and seventy-seven patients were submitted to 525 craniotomies for treatment of 630 intracranial aneurysms. The majority of patients were female (72.1%) in the fourth or fifth decade of life. Anterior circulation aneurysms were more common (94.4%). The most common location for the aneurysm was the middle cerebral artery bifurcation. The patients were followed by a period from 1 month to 5 years. The outcome was measured by the Glasgow Outcome Scale (GOS). At discharge, 62.1% of the patients were classified as GOS 5, 13.9% as GOS 4, 8.7% as GOS 3, 1.7% as GOS 2 and 14.8% as GOS 1.